Histopathological study of skin lesions in tertiary care hospital - Mithila, K. B.; Priya, G. Yamini; Anuradha, V.; Sreedhar, Vijaya (International Journal Of Community Medicine And Public Health, 2025)
Background: Skin disorders represent a significant health challenge, with varied clinical presentations and potential impacts on patient quality of life. This study aims to investigate the distribution and prevalence of skin lesions through histopathological examination in a tertiary care hospital setting. Methods: A retrospective study was conducted from June 2021 to June 2023 in the Department of Pathology at Bhaskar Medical College, Hyderabad. All skin biopsy samples received during this period were processed using standard Hematoxylin and Eosin staining techniques. Data analysis was performed using MedCalc Version 10.0 for Windows. Sequential sampling was employed, analyzing all available samples during the study period. Results: A total of 80 cases were examined, with 42 females (54%) and 38 males (46%). The 16-30 age group represented the majority (35%). Non-neoplastic lesions predominated (96.2%), with lichen planus being the most common diagnosis (18.7%), followed by intradermal nevus (8.7%). Neoplastic lesions accounted for 3.8%, with basal cell carcinoma (2.5%) being the most frequent. Conclusions: Histopathological examination proves crucial in accurately diagnosing skin lesions, highlighting the importance of clinicopathological correlation for effective patient management.